2019
DOI: 10.1161/hypertensionaha.119.12762
|View full text |Cite
|
Sign up to set email alerts
|

Renal Inflammation in DOCA-Salt Hypertension

Abstract: Recent reports indicate that, in addition to treating hypertension, renal denervation (RDN) also mitigates renal inflammation. However, since RDN decreases renal perfusion pressure, it is unclear whether these effects are due to the direct effects of RDN on inflammatory signaling or secondary to decreased arterial pressure (AP). Therefore, this study was conducted to elucidate the contribution of renal nerves to renal inflammation in the DOCA-salt rat, a model in which RDN decreases AP and abolishes renal infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 51 publications
4
22
0
Order By: Relevance
“…During this process, kidney is a major organ for BP homeostasis. Recently, there is a growing body of evidence suggesting that inflammation plays a crucial role in the progression of salt-sensitive hypertension as well as kidney dysfunction 3 5 . In experimental models, salt-sensitive hypertension are associated with the accumulation and activation of T cells in the kidney, which produces inflammatory cytokines including IFN-γ, IL-17, and TNF-α; results in sodium retention, vasoconstriction and enhanced oxidative stress; and then promotes hypertension, glomerular injury, renal fibrosis, and dysfunction 6 .…”
Section: Introductionmentioning
confidence: 99%
“…During this process, kidney is a major organ for BP homeostasis. Recently, there is a growing body of evidence suggesting that inflammation plays a crucial role in the progression of salt-sensitive hypertension as well as kidney dysfunction 3 5 . In experimental models, salt-sensitive hypertension are associated with the accumulation and activation of T cells in the kidney, which produces inflammatory cytokines including IFN-γ, IL-17, and TNF-α; results in sodium retention, vasoconstriction and enhanced oxidative stress; and then promotes hypertension, glomerular injury, renal fibrosis, and dysfunction 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms responsible for the antihypertensive effect of RDNX are still unclear. Our laboratory and others have previously reported that specifically targeting afferent renal nerves in DOCA-salt model 35 37 or efferent nerves in Dahl salt sensitive rats 24 chronically lower MAP. Similar studies would be necessary to identify which type of renal nerves (afferent or efferent) are important in BPH/2J mice.…”
Section: Discussionmentioning
confidence: 81%
“…However, there is conflicting evidence concerning the distinctive contribution of renal afferent and efferent nerves on the described anti-inflammatory effects of RDN. Xiao et al (2015) could not find a contribution of afferent nerves on Ang II-induced hypertension and renal inflammation, whereas Banek showed evidence that renal afferent nerves modulate at least in part renal inflammation in DOCAsalt hypertension (Banek et al, 2016(Banek et al, , 2019. In another study, performed in global α2A-deficent mice chronically infused with a high dose of Ang II, increased renal sympathetic norepinephrine release impairs renal function and aggravates hypertension as well as renal fibrosis without affecting the amount of infiltrating immune cells (Hering et al, 2020).…”
Section: Role Of Renal Sympathetic Neurotransmission and α2-adrenocepmentioning
confidence: 98%
“…In hypertension as well as acute or chronic kidney damage, stimulation of renal nociceptive afferent nerves mediate an increase in sympathetic nerve activity leading to a further activation of RSNA and subsequently to a progression of hypertension and hypertensive kidney disease. Thus, several other factors such as pro-inflammatory cytokines ( Banek et al, 2019 ), uremic toxins ( Campese and Kogosov, 1995 ), and hypoxia ( Dibona and Kopp, 1997 ; Soukhova-O'hare et al, 2006 ; Saha et al, 2019 ) can activate the chemo- and mechano-sensitive afferent nerves leading to an increased RSNA. Activation of afferent nerves under pathophysiological conditions such as acute kidney injury induced by a phenol injection into the kidney causes hypertension by increasing RSNA via afferent renal nerve stimulation ( Ye et al, 2002a , b ; Leong et al, 2006 ).…”
Section: Mechanisms Regulating Renal Sympathetic Nerve Activitymentioning
confidence: 99%
See 1 more Smart Citation